A new eco-friendly chemical treatment of natural fibres: Effect of sodium bicarbonate on properties of sisal fibre and its epoxy composites. (February 2016) - Fiore, V.; Scalici, T.; Nicoletti, F.; Vitale, G.; Prestipino, M.; Valenza, A.
Abstract: Several researchers have shown how sisal fibres possess remarkable tensile properties that yield them good candidates as reinforcement in biocomposite materials. This work aims to evaluate the effect of an eco-friendly and cost effective surface treatment method based on the use of commercial sodium bicarbonate (i.e. baking soda) on properties of sisal fibre and its epoxy composites. In particular, raw sisal fibres were treated with a 10%w/w of sodium bicarbonate solution for different periods (24, 120 and 240 h), at room temperature. Changes occurring in sisal fibres were characterized through scanning electron microscope, Fourier transform infrared spectroscopy, thermogravimetric analysis and helium pycnometer analysis. The mechanical characterization of sisal fibre was carried out through single fibre tensile tests and a reliability analysis of the experimental data was performed. A mathematical model was also applied to investigate the relation between the transverse dimension of the fibres and their tensile properties. Interfacial adhesion of sisal fibre with an epoxy matrix was investigated using single fibre pull out technique. Moreover, to deeper investigate the effect of the proposed treatment, epoxy based composites reinforced with short randomly oriented sisal fibres were manufactured and characterized by means of quasi-static flexural tests. The experimental results showed that 120 h is the optimum time for treating sisal fibre to achieve highest interfacial adhesion and mechanical properties with epoxy matrix.